Active and passive tumor targeting via micellar dendritic constructs - Sümer, Burcu. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
Among many other nanotherapeutics, polymeric micellar systems are emerging as a very important class of nano-pharmaceuticals due to their ability to improve pharmacokinetics and bio-distribution of chemotherapy drugs as well as to reduce related systemic toxicities. In this thesis three such systems are presented in terms of synthesis, characterization and in vitro activity. In the first one, drug conjugated micellar constructs are fabricated using triblock dendron-polymer conjugates where a hydrophilic linear polyethylene glycol (PEG) chain is flanked by well-defined hydrophobic biodegradable polyester dendrons bearing an anti-angiogenic drug, combretastatin-A4 (CA4). Variation in dendron generation is utilized to obtain a library of micellar constructs with varying sizes and drug loadings. For the second project a cRGDfK targeting group was introduced to micelle shell to achieve active targeting cancer cells over-expressing αυβ3/αυβ5 integrins. Non-toxic, biodegradable, and modularly tunable micellar delivery systems were generated using two dendron-polymer based components. Either an AB type dendronpolymer construct or an ABA type dendron-polymer-dendron conjugate was used as primary construct; along with an AB type dendron-polymer containing a cRGDfK targeting group. In the final section another micellar delivery system was generated with conjugated Trastuzumab antibody which is used as treatment against tumor cells expressing HER2 receptors. Incorporation of this therapeutic antibody to nano drug delivery systems can improve its target specificity further. As a result three systems were generated with different drug release profiles ranging between days to hours depending on loading strategy. Polyester dendron cores rendered them acid labile as well as stable in terms of CMC. Their sizes were in the range of EPR controllable by core components as needed. Furthermore complex targeting groups were introduced to improve the cell uptake profiles further. In conclusion generated micellar platforms exhibited suitable physical and biological characteristic indicating their potential as drug delivery systems.
Keywords: Micelles.; Tumors.